Azilsartan compared to ACE inhibitors in anti-hypertensive therapy: one-year outcomes of the observational EARLY registry. Issue 1 (December 2016) - Gitt, Anselm; Bramlage, Peter; Potthoff, Sebastian; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ehmen, Martina; Ouarrak, Taoufik; Senges, Jochen; Schmieder, Roland
Abstract Background Azilsartan medoxomil (AZL-M), has been demonstrated to be more effective than the other sartans currently in use; however, there is insufficient information available comparing it with ACE-inhibitors. Therefore, we aimed to compare the efficacy, safety, and tolerability of AZL-M with that of ACE-inhibitors in a real life clinical setting. Methods The EARLY registry is a prospective, observational, national, multicentre registry with a follow-up period of 12 months. There were two principal objectives: 1) documentation of the achievement of target BP values set according to recent national and international guidelines, and 2) description of the safety profile of AZL-M. Results A total of 3 849 patients with essential arterial hypertension were recruited from primary care offices in Germany. Patients who initiated monotherapy at baseline comprising either AZL-M or an ACE-inhibitor were included at a ratio of seven to three. Results demonstrated that a blood pressure target of <140/90 mmHg was achieved by a significantly greater proportion of patients in the AZL-M group (61.1 %) compared with the ACE-inhibitor group (56.4 %;p < 0.05; OR, 1.21; 95 % CI, 1.03–1.42), with this finding maintained after adjusting for differences in baseline characteristics. AZL-M appeared to have an equivalent safety profile to the ACE-inhibitors, with a similar incidence of adverse events in the two patient groups (p = 0.73). Conclusions These data add to the results of previous randomized controlled clinical trials suggesting that, compared with other agents that target the renin–angiotensin system, AZL-M provides statistically significant albeit small improvements in blood pressure control.